2018
DOI: 10.3390/biom9010001
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Insights into the Function of Kinesin-8 Proteins in Microtubule Length Regulation

Abstract: Proper regulation of microtubules (MTs) is critical for the execution of diverse cellular processes, including mitotic spindle assembly and chromosome segregation. There are a multitude of cellular factors that regulate the dynamicity of MTs and play critical roles in mitosis. Members of the Kinesin-8 family of motor proteins act as MT-destabilizing factors to control MT length in a spatially and temporally regulated manner. In this review, we focus on recent advances in our understanding of the structure and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 102 publications
(208 reference statements)
1
13
1
Order By: Relevance
“…This brief report presents some of the biochemical properties of the DdKif10 motor. Previous works in other organisms indicate that Kinesin-8 isoforms are relatively slow, plus-end directed motors, some with distinctive MT depolymerization activities [2]. We show, here, in vitro gliding and ATPase activities, as well as the in vivo localization of a motor fragment.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…This brief report presents some of the biochemical properties of the DdKif10 motor. Previous works in other organisms indicate that Kinesin-8 isoforms are relatively slow, plus-end directed motors, some with distinctive MT depolymerization activities [2]. We show, here, in vitro gliding and ATPase activities, as well as the in vivo localization of a motor fragment.…”
Section: Introductionsupporting
confidence: 64%
“…Kinesin-8 motors are generally considered slow, processive, and accumulate at the MT plus ends where they effect tip dynamics [2]. Our results indicate that the DdKif10 motor domain can move MTs in vitro at about the same rate as the human Kinesin-8 isoform (170 nm/s (Dd) vs. 128-299nm/s (HsKif18A [28])).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The importance of Kinesin-8 molecular motors in mitosis in many eukaryotes is wellestablished. These motors move on spindle MTs towards their plus end and regulate spindle dynamics, contributing to spindle length and positioning, and thus to chromosome alignment during metaphase [44][45][46]. Although the exact molecular basis of these functions remains controversial, Kinesin-8s modulate MT dynamics and may either stabilise, destabilise, slow growth, or actively depolymerize MTs in spindle function [18,19,47].…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic studies identified 3 kinesins expressed during male gametogenesis (kinesin-8B, -13 and -15)(Khan et al, 2005;Talman et al, 2014), but no functional studies have been conducted until now. In other eukaryotes, orthologues for kinesin-4, -5, -8B, -13 and -15 are known to be involved in microtubule dynamics and particularly mitosis and cilia/flagella length regulation(Almeida & Maiato, 2018;Hu et al, 2015;Ma, Wang, & Yang, 2017;Muhia et al, 2016;Niwa, 2015;Niwa et al, 2012;Shrestha, Hazelbaker, Yount, & Walczak, 2018;Singh, Pandey, Al-Bassam, & Gheber, 2018;van Riel et al, 2017). Unfortunately, concerning PBANKA_0622400, PBANKA_0609500, PBANKA_0809500, PBANKA_0902400 and PBANKA_1224100, no functional data are available and the number of species possessing orthologues of these proteins is currently very limited, making it difficult to construct any hypothesis concerning their roles.…”
mentioning
confidence: 99%